A storytelling of the efficiency of agroecological practices for cacao production in Ucayali, Peru - Orjuela Ramirez, Guillermo (2024)
These storytelling shows the results of a study that estimates the efficiency of agroecological practices implemented by cocoa producers in the region of Ucayali, Peru. We use the “Agroecological practices characterization survey” of the CGIAR Initiative on Agroecology to assess the efficiency of agroecological practices in 654 cacao producers, in terms of resource use and output production.